Adsorption of phenol by activated carbon: Influence of activation methods and solution pH - Beker, Ulker; Ganbold, Batchimeg; Dertli, Halil; Gulbayir, Dilek Duranoglu (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Cherry stone based activated carbon derived from a canning industry was evaluated for its ability to remove phenol from an aqueous solution in a batch process. A comparative adsorption on the uptake of phenol by using commercial activated carbon (Chemviron CPG-LF), and two non-functional commercial polymeric adsorbents (MN-200 and XAD-2) containing a styrene-divinylbenzene macroporous hyperreticulated network have been also examined. Equilibrium studies were conducted in 25 mg L-1 initial phenol concentrations, 6.5-9 solution pH and at temperature of 30 degrees C. The experimental data were analyzed by the Langmuir and Freundlich isotherm models. Besides, the cherry stone based activated carbons were carried out by using zinc chloride and KOH activation agents at different chemical ratios (activating agent/precursor), to develop carbons with well-developed porosity. The cherry stone activated carbon prepared using KOH as a chemical agent showed a high surface area. According to the results, activated carbons had excellent adsorptive characteristics in comparison with polymeric sorbents and commercial activated carbon for the phenol removal from the aqueous solutions. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Pyrolysis; Renewability; Activated carbon; Adsorption; Phenol; ENERGY; Thermodynamics; Energy & Fuels; Mechanics